EXPRESSION OF HAS GEN CODING FOR HEMAGGLUTININ (HA) ANTIGEN OF INFLUENZA VIRUS A/H5N1 IN ESCHERICHIA COLI - Huyền, Đỗ Thị (Vietnam Journal of Biotechnology, 2011)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Influenza virus is a highly contagious and acute respiratory disease with a high degree of morbidity and mortality. The highly pathogen subtype of H5N1 is currently circulating throughout many countries in the world. In this research, we studied on expression of the ha5-0 gene coding for hemagglutinin of avian influenza A/H5N1 in E. coli BL21 cell. The ha5-0 gene was fiised with trx gene coding for Thioredoxin in pET22trx and was constructed in two different forms: 1) The whole native ha5-0 gene except codon ATG and signal peptide; 2) Replaced the cleavage site between HAI and HA2 by the artificial polylinker (ha5-l-2). The expression of recombinant strains habouring gene ha5-0 or ha5-l-2 was studied in LB medium with the addition of ampicillin and IPTG. The effects of concentration of induction factor IPTG (0; 0,05; 0,1; 0,2; 0,4; 0,6; 0,8; 1; 1,5 and 2 mM) and temperature (22, 25, 28, 30, and 37°C) were investigated. The obtained results have showed that, the fusion protein of TrxHa5-0 and TrxHa5-l-2 with the molecular mass of 66 kDa were synthesized successfiiUy in E. coli BL21 cells at 25°C with the regulation of T7 promoter which is induced by IPTG. These recombinant proteins were not observed when IPTG was not added into the medium and it was synthesized when IPTG was added even with a very low concentration (0.05 mM). However, the expression level was not increased linearly with the increasing of concenfration of IPTG. Interestingly, TrxHa5-l-2 was expressed at the higher level and higher proportion of soluble form in compare with TrxHa5-0. The solubility of TrxHa5-l-2 was over 70% as expressing at the temperature of 25°C. This gene construct will be integrated into the genome of P. pastoris in order to create a sub unit vaccine protect poultry against influenza virus.